Depressive Symptoms, Co-Morbidities, and Glycemic Control in Hong Kong Chinese Elderly Patients With Type 2 Diabetes Mellitus - Fung, Annie C. H.; Tse, Gary; Cheng, Hiu Lam; Lau, Eric S. H.; Luk, Andrea; Ozaki, Risa; So, Tammy T. Y.; Wong, Rebecca Y. M.; Tsoh, Joshua; Chow, Elaine; Wing, Yun Kwok; Chan, Juliana C. N.; et al. (Frontiers in Endocrinology, 2018)
Background and objectives: Undiagnosed depression is an important comorbidity in type 2 diabetes (T2D) which can be detected using the Geriatric Depression Scale (GDS-15) questionnaire. In this cross-sectional study, we examined the associations of depression using GDS score with control of cardiometabolic risk factors and health status in elderly patients with T2D. Setting and participants: Between February and December 2013, patients aged ≥65 years who underwent structured comprehensive assessment as a quality improvement programme at the Diabetes Centre of a teaching hospital were invited to complete the GDS-15 questionnaire. Main outcome measures: Depression was defined as a GDS score ≥7. Demographic data, prior history of co-morbidities, frequency of self-reported hypoglycemia and attainment of treatment targets defined as HbA1c,<7%, blood pressure<130/80 mmHg and LDL-C<2.6 mmol/L were documented. Results: Amongst 325 participants (65% male, median [interquartile range] age: 69 [8] years), 42 (13%) had depression. Patients with depression had longer disease durations (mean±SD: 15.1±9.1 vs. 11.6±8.1 years, P=0.02), more frequent self-reported hypoglycemic events (17% vs. 6%, P=0.03) and were less likely to attain all three treatment targets (0% vs. 16%, P=0.004) than those without depression. On multivariable analysis, patients with depression had an odds ratio of 2.84 (95% confidence intervals: 1.35 to 6.00, P=0.006) of reporting prior history of co-morbidities. Conclusion: In elderly patients with T2D, depression was not uncommon especially in those with poor control of risk factors, hypoglycemia and co-morbidities. Inclusion of GDS-15 questionnaire during structured assessment for complications and risk factors can identify these high-risk patients for more holistic management of their physical and mental health.